Primary cutaneous apocrine carcinoma in a 50-year old male - Matthew Crabtree; Doris Cheng; Caleb Jeon; Anamaria Munteanu; Kumkum Vadehra; Richard Chiu; Rose Venegas; Jan Smogorzewski; Paul Shitabata; Shi-Kaung Peng (Human Pathology Reports, 2021)
Primary cutaneous apocrine carcinoma (PCAC) is a rare apocrine neoplasm that is challenging to diagnose due to its histologic and immunophenotypic overlap with other tumors, most notably metastatic breast carcinoma, and also bladder carcinoma. We present a case of a 50-year old male with an axillary mass diagnosed as primary apocrine carcinoma after surgical excision. Immunohistochemical evidence as well as clinical data were used to arrive at the final diagnosis of PCAC.